microRNA-1273g-3p is a useful non-invasive test for the prediction of liver fibrosis in patients with chronic hepatitis C - Nan, Yuemin (Exp Ther Med, 2019)
Previous studies using microRNA (miRNA or miR) microarrays have demonstrated that miR-1273g-3p is upregulated in patients with hepatitis C virus (HCV)-associated fibrosis. As miRNAs have been suggested to be promising non-invasive biomarkers, the aim of the present study was to assess whether miR-1273g-3p may be useful as a potential indicator of fibrosis progression in patients with HCV. Liver biopsies were performed on 112 patients with chronic hepatitis C (CHC) and liver stiffness measurements (LSM) were performed using FibroTouch. Liver fibrosis was determined based on Meta-analysis of Histological Data in Viral Hepatitis classification, and the aspartate aminotransferase (AST)-to-platelet count (PLT) ratio index (APRI) and Fibrosis-4 score (FIB-4) were calculated. The diagnostic performance of miR-1273g-3p, LSM, APRI and FIB-4 in predicting fibrosis stage were evaluated and compared by receiver operating characteristic (ROC) analysis. It was demonstrated that miR-1273g-3p levels were significantly positively correlated with the liver fibrosis stage (r=0.657, P<0.001). The results of LSM, APRI and FIB-4, the three non-invasive diagnostic methods, had good consistency with liver biopsy results, and their correlation coefficients with fibrosis staging were 0.815, 0.417 and 0.522, respectively. The areas under the ROC curves of miR-1273g-3p for F≥2 and F=4 stage samples were 0.841 and 0.933, respectively, which were lower than LSM (0.890 and 0.937), and higher than FIB-4 (0.791 and 0.766) and APRI (0.719 and 0.760). Spearman analysis demonstrated that serum miR-1273g-3p levels were significantly positively correlated with age, body mass index, alanine aminotransferase, AST and total bilirubin (all P<0.05), and negatively correlated with PLT (P<0.05). However, no significant correlation was observed between miR-1273g-3p levels, baseline HCV RNA loads and genotype. Therefore, the results demonstrated that miR-1273g-3p levels, as a novel non-invasive test, may be a useful and easy method for predicting the stage of liver fibrosis in patients with CHC, and has a better diagnostic performance than FIB-4 and APRI. Further prospective studies are required to validate the efficacy of miR-1273g-3p as a predictor of liver fibrosis.